Sugar score and dental caries experience among high school children - Dr. Divya Bhavani Vasamsetti; Dr. Devaki Talluri; Dr. Srinivas Pachava (International Dental Journal, 2023)
Aim or Purpose: To know the association between sugar score and dental caries experience among high school children in East Coastal Region of India. Materials and Methods: A cross-sectional questionnaire study with clinical examination was carried out on 750 high school children. Ethical clearance was obtained from the Institutional Ethics Committee, SIBAR Institute of Dental Sciences and was later approved by the Nandamuri Taraka Rama (NTR) University of Health Sciences, Vijayawada (Pr.201/IEC/SIBAR/2019-D190030903). Dental caries was measured using WHO criteria (1997) and sweet score was measured using the Nizel and Papas 24 hour diet approach. Chi-square test, Mann-Whitney U test, spearman correlation test, and binary logistic regression were utilized for factual investigation with level of significance at p<0.05. Results: With mean age as 14.9 ± 0.693, the children mean DMFT was 0.72 ± 1.06 and children with one and two carious lesions were 169 (22.3%) and 91 (12.1%) respectively, for a total prevalence of 39.2%. Only 233 children (31.1%) had no sugar exposure at all per day while 38.1% having one sugar exposure per day. The sweet score was excellent in 488 (65.1%) subjects, with few pupils (4%) in the ''Watch out zone'' with a statistically significant (P = 0.0001) relationship between DMFT, daily sugar exposure frequency, and the sweet score. Conclusions: Low sugar scores and dental caries experience in the study population reflects controlled environment on diet and hygiene practices. However, a strong primary message regarding the harmfulness of sugar in non-communicable diseases should be conveyed to children because there is direct observation between the frequency of sugar consumption and dental caries.